Development and validation of a chromatographic method for the detection and quantification of Ivermectin residues in wastewater - Colque-Ayma, Elvis Jack (2023)
This study developed and validated a method of analysis by UHPL-DAD to detect and quantify Ivermectin (IVM) residues in wastewater. The implementation of this method consisted of a robust and efficient method, where the retention time for this residue was 3.1 min. However, the parameters considered in the validation process of the analytical method were: selectivity, linearity, detection limit, quantification limit and recovery percentage; the method is selective, the correlation coefficient is R2 ≥ 0.99, it presents a detection limit (LD) of 0.003 µg L-1, a quantification limit (LQ) of 0.01 µg L-1, and a recovery percentage of 90% (with fortification of 0.1 µg L-1).